Cystic Fibrosis Transmembrane Regulator Correctors and Potentiators - Rowe, Steven M. (Cold Spring Harbor Laboratory Press, 2013)
Cystic fibrosis (CF) is caused by loss-of-function mutations in the CF transmembrane conductance regulator (CFTR) protein, a cAMP-regulated anion channel expressed primarily at the apical plasma membrane of secretory epithelia. Nearly 2000 mutations in the CFTR gene have been identified that cause disease by impairing its translation, cellular processing, and/or chloride channel gating. The fundamental premise of CFTR corrector and potentiator therapy for CF is that addressing the underlying defects in the cellular processing and chloride channel function of CF-causing mutant CFTR alleles will result in clinical benefit by addressing the basic defect underlying CF. Correctors are principally targeted at F508del cellular misprocessing, whereas potentiators are intended to restore cAMP-dependent chloride channel activity to mutant CFTRs at the cell surface. This article reviews the discovery of CFTR potentiators and correctors, what is known regarding their mechanistic basis, and encouraging results achieved in clinical testing.